How Does Domino Card Help Children to Insight Numbering - Wulan Saroinsong; Novi Anggraeni; Iqlima Mulia Putri (SEA-CECCEP, 2021)
This study explores the differences in the effectiveness of conventional educational domino media and contemporary digital educational domino media on the cognition of children aged 4-6 years. This research was conducted using R&D (research Research and Development) using the ASSURE model. 34 children aged 4-6 years and their parents were involved in the small socialization stage using a questionnaire conducted by Google Form. In this test, the researcher used SPSS 23 to test the feasibility of the media. The first test is the Validity Test of parents' perceptions and the results of children's cognitive abilities related to the ability to match number symbols with numbers for children aged 4-6 with a sig level of 0.05 with the results of r above (0.17) on each item being declared valid because r table > r count. The second test is the Validity Test of parental feedback on conventional educational domino media and contemporary digital education domino media with the results of r above (0.17) for each item being declared valid because r table > r count. The third test is the Cronbach's Alpha Reliability Test which results in the effectiveness of conventional domino media being 0.631, while the effectiveness of contemporary domino media is 0.516. The results of the cognitive abilities of children who use conventional media are 0.740, while the cognitive abilities of children who use contemporary media are 0.635. The fourth test is the Classical Assumption Test with the Normality Test, the sig value is above 0.05, the data is normally distributed, the homogeneity test is the sig value above 0.05, then the data is said to have the same variance (homogeneous). The fifth test is the Correlation Test with results less than 0.05 which means it has a significant strong relationship for conventional domino media 0.671 while for digital domino media 0.922. The sixth test is the Sample T-test with the results of the same contemporary media significance, which is less than sig 0.05. The result of the average score is that there is a difference in scores between conventional and contemporary domino media. Where the average score of contemporary digital domino media (27.76) is greater than conventional domino media (25.47). In this test, it can be decided if conventional and contemporary digital domino media are very effective in the ability to match number symbols with numbers in children aged 4-6 years. Recent research confirms that the conventional and contemporary design domino media model has contributed to the improvement of children's cognition so that it is feasible and effective to use. Furthermore, this research has implications for the term positive benefits of digital media, where children's cognitive development is formed through game stimulation. However, gamification learning will be effectively implemented in fostering children's cognitive development.